2014
DOI: 10.3389/fnhum.2014.00951
|View full text |Cite
|
Sign up to set email alerts
|

Combined action observation and imagery facilitates corticospinal excitability

Abstract: Observation and imagery of movement both activate similar brain regions to those involved in movement execution. As such, both are recommended as techniques for aiding the recovery of motor function following stroke. Traditionally, action observation and movement imagery (MI) have been considered as independent intervention techniques. Researchers have however begun to consider the possibility of combining the two techniques into a single intervention strategy. This study investigated the effect of combined ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 55 publications
5
78
0
1
Order By: Relevance
“…Action observation (AO) training consists of observing an action conducted by others without any motor output . Both MI and AO have been shown to promote motor learning, demonstrating neurophysiological activation of the brain areas corresponding to motor planning and voluntary movement . Acute effects of AO and MI interventions filmed from the first‐person visual perspective have also been shown to optimize kinetic and kinematic variables and promote motor learning .…”
Section: Introductionmentioning
confidence: 99%
“…Action observation (AO) training consists of observing an action conducted by others without any motor output . Both MI and AO have been shown to promote motor learning, demonstrating neurophysiological activation of the brain areas corresponding to motor planning and voluntary movement . Acute effects of AO and MI interventions filmed from the first‐person visual perspective have also been shown to optimize kinetic and kinematic variables and promote motor learning .…”
Section: Introductionmentioning
confidence: 99%
“…This is an unexpected result given previous findings that typically show a reduction in mu rhythm magnitude during tasks involving sensorimotor processes (Nedelko et al, 2012; Villiger et al, 2013; Kondo et al, 2015). Several studies of II have found it to be associated with increased motor cortex excitability (Sakamoto et al, 2009; Ohno et al, 2011; Tsukazaki et al, 2012; Wright et al, 2014), and increased activation of the motor network more broadly (Nedelko et al, 2012; Villiger et al, 2013), when compared to MI or AO alone. One explanation for the lack of ERD/S values <0 is that engaging with the present NFB system while performing II was too cognitively demanding, hindering subjects' performance of II.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have used a combined MI/AO approach: here an individual watches a motor task being performed repetitively, while simultaneously imagining they are performing the movement themselves. This approach of “Imagined Imitation” (II) has been shown to facilitate corticospinal excitability to a greater degree than either AO or MI alone (Sakamoto et al, 2009; Ohno et al, 2011; Tsukazaki et al, 2012; Wright et al, 2014), and to increase brain activity in several regions critical for motor learning and performance over and above that seen in AO or MI (Macuga and Frey, 2012; Nedelko et al, 2012; Villiger et al, 2013; Kondo et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…First, corticospinal excitability, measured through the amplitudes of motor evoked potentials, during both AO and MI of hand gestures is reliably higher than control conditions (e.g., Clark et al, 2004; Williams et al, 2012; see Naish et al, 2014; Grosprêtre et al, 2016 for reviews). Second, AO+MI produces significantly greater facilitation of corticospinal excitability compared to AO (Ohno et al, 2011; Wright et al, 2014, 2016) and, in some cases, MI as well (Sakamoto et al, 2009; Tsukazaki et al, 2012; Mouthon et al, 2015). These effects have been demonstrated across a variety of tasks, including simple and sequential finger movements (Wright et al, 2014, 2016), gross and fine motor tasks (Sakamoto et al, 2009; Ohno et al, 2011) and coordination tasks (Tsukazaki et al, 2012; Mouthon et al, 2015).…”
Section: The Effects Of Motor Imagery During Action Observation: Empimentioning
confidence: 99%
“…Several studies have filmed the AO component from a first-person visual perspective (e.g., Villiger et al, 2013; Wright et al, 2014, 2016), while other studies have filmed the action from a third-person visual perspective (e.g., Eaves et al, 2014, 2016; Mouthon et al, 2015; Taube et al, 2015). In some cases, participants are instructed to explicitly image from a first person perspective, while in other cases they are only told to imagine themselves performing the observed movement, which may result in participants adopting either a first- or third-person imagery perspective, depending on their imagery perspective preference.…”
Section: Future Research Opportunitiesmentioning
confidence: 99%